STRATEGI PEMUNGUTAN PENERIMAAN PAJAK REKLAME KOTA BEKASI - Ichsan, Aulia; Siregar, Hermanto; Soetarto, Endriatmo (Jurnal Manajemen Pembangunan Daerah, 2018)
One of the efforts of Local Government in financing regional development is through local taxes. Bekasi City is a cross-trade City and its strategic location has great potential to be able to maximize local revenue through the local tax sector, e.g. advertisement tax. The purpose of this research was to determine the growth rate and the contribution of advertisement tax to local taxes, measure the effectiveness and efficiency of advertisement tax, and determine the strategy in the implementation of revenue advertisement tax collections. Analysis methods of this research includes calculation of growth and contribution ratio as well as effectiveness and efficiency ratio and the analytical hierarchy process (AHP). Results of this research show that the growth rate of advertisement tax in Bekasi City average 20.65% and its contribution to local taxes average of 3.52% with the average effectiveness rate 82.20% (“quite effective”) and the efficiency level 6.31% (“highly efficient”). It is suggested from the AHP results that the Local Government of Bekasi City should implement a strategy of improving the quality and quantity of human resources as well as a strategy of improving technical guidelines on advertisement tax collection.Keywords : advertisement tax, growth and contribution, effectiveness and  efficiency, strategy, Bekasi City.